Unveiling the biomechanical characteristics of uke in seoi-nage: objective metrics for enhancing judo performance - Ishii, T.; Koshida, S. (Research Journal of Budo, 2025)
Judo, widely recognized as an Olympic sport, was defined as a "way" that maximizes the efficient use of physical and mental energy (Seiryoku-Zenyo`). This path encompassed the principle of ?Jita-Kyoei` (mutual prosperity), fostering harmony between individuals and society. While grounded in philosophical ideals, the teaching and execution of judo techniques required rigorous scientific analysis. This study investigated the biomechanics of seoi-nage, a highly effective and widely practiced technique, aiming to establish objective performance benchmarks. Nineteen experienced male judo athletes, including World Championship medallists, participated in this research. Using an 18-camera Vicon T10 system operating at 250 Hz and two Kistler force platforms sampling at 1000 Hz, the study captured three-dimensional motion data and ground reaction forces during the execution of seoi-nage. Performance metrics included the displacement of the uke`s center of mass (COM), total body linear momentum, and angular momentum. Key findings indicated that during seoi-nage, the uke`s COM showed a slight vertical increase during the turning phase and a significant decrease during the throwing phase, emphasizing forward and downward movements. Linear momentum analysis revealed substantial increases in resultant momentum, driven primarily by vertical and anterior-posterior components, with minor changes in the medial-lateral direction. Angular momentum analysis demonstrated significant increases, particularly in the medial-lateral direction, highlighting the critical role of rotational dynamics. Three hypotheses were tested: 1) The vertical component of uke`s momentum as a proficiency index, 2) The angular momentum of uke as a proficiency index, and 3) The mean moment of force as a proficiency index. Results indicated that the vertical momentum component was unreliable due to high variability and weak correlation with angular impulse. In contrast, angular momentum and mean moment of force were validated as reliable indicators of technical proficiency, correlating with effective execution. This study provides a biomechanical basis for evaluating and improving judo seoi-nage. By identifying critical metrics such as angular momentum and the moment of force related to angular impulse, the research highlights key indicators of technical proficiency. These findings offer valuable insights for developing targeted training programs aimed at enhancing performance outcomes. Future research should expand on these results by including more techniques and athletes, integrating advanced technologies to further refine analyses. These insights pave the way for more effective training strategies, contributing to the evolution of judo as a sport and discipline.